2005
DOI: 10.1093/hmg/ddi266
|View full text |Cite
|
Sign up to set email alerts
|

The first molecular details of ALT in human tumor cells

Abstract: The activation of a telomere maintenance mechanism (TMM) is indispensable for cellular immortalization, a hallmark of human cancer. Although most human cancers use telomerase as their TMM, some use an alternative lengthening of telomeres (ALT) mechanism. The latter especially include specific subtypes of soft tissue sarcomas where ALT occurs most often in tumors with complex karyotypes, astrocytic brain tumors and osteosarcomas. The prognostic significance of ALT varies according to the type of tumor. Some ALT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
157
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 197 publications
(166 citation statements)
references
References 40 publications
5
157
0
3
Order By: Relevance
“…It was shown that telomeres in tumor cells commonly manifest telomere dysfunction, and chromosomal aberrations indicative of these defects are observed. Telomerase is activated in 85% of the tumors, while it is not present in the rest of the tumors, some of which have demonstrated alternative lengthening of telomeres (ALT) [Muntoni and Reddel, 2005].…”
Section: Telomere Organization In Tumor Cellsmentioning
confidence: 99%
“…It was shown that telomeres in tumor cells commonly manifest telomere dysfunction, and chromosomal aberrations indicative of these defects are observed. Telomerase is activated in 85% of the tumors, while it is not present in the rest of the tumors, some of which have demonstrated alternative lengthening of telomeres (ALT) [Muntoni and Reddel, 2005].…”
Section: Telomere Organization In Tumor Cellsmentioning
confidence: 99%
“…Telomerase is a reverse transcriptase that synthetizes telomere repeats de novo at the chromosome ends (reviewed in Blackburn, 2001;Collins and Mitchell, 2002;Blasco, 2005) and in this way regulates the length of telomeric repeats. An alternative mechanism for telomere elongation is the so-called alternative lengthening of telomeres or ALT mechanism (reviewed in Muntoni and Reddel, 2005), which relies on homologous recombination events at telomeres (Dunham et al, 2000;Bailey et al, 2004;Bechter et al, 2004). ALT cells are characterized by long and heterogeneous telomeres, increased telomere recombination frequencies, as well as by the colocalization of telomeres with the PML bodies forming the so-called ALT-associated PML bodies or APBs (reviewed in Dunham et al, 2000;Bechter et al, 2004;Bailey et al, 2004;Muntoni and Reddel, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative mechanism for telomere elongation is the so-called alternative lengthening of telomeres or ALT mechanism (reviewed in Muntoni and Reddel, 2005), which relies on homologous recombination events at telomeres (Dunham et al, 2000;Bailey et al, 2004;Bechter et al, 2004). ALT cells are characterized by long and heterogeneous telomeres, increased telomere recombination frequencies, as well as by the colocalization of telomeres with the PML bodies forming the so-called ALT-associated PML bodies or APBs (reviewed in Dunham et al, 2000;Bechter et al, 2004;Bailey et al, 2004;Muntoni and Reddel, 2005). Telomerase is undetectable in most somatic tissues with the exception of stem cell compartments and some highly proliferative cell types (reviewed in Flores et al, 2006), where telomerase levels are not sufficient to prevent the progressive telomere shortening associated with age (Harley et al, 1990;Canela et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations